Bone Marrow-Derived Mesenchymal Stromal Cell Therapy in Severe COVID-19: Preliminary Results of a Phase I/II Clinical Trial - Grégoire, Céline; Layios, Nathalie; Lambermont, Bernard; Lechanteur, Chantal; Briquet, Alexandra; Bettonville, Virginie; Baudoux, Etienne; Thys, Marie; Dardenne, Nadia; Misset, Benoît; Beguin, Yves (Frontiers in Immunology, 2022)
Background Treatment of acute respiratory distress syndrome (ARDS) associated with COronaVIrus Disease-2019 (COVID-19) currently relies on dexamethasone and supportive mechanical ventilation, and remains associated with high mortality. Given their ability to limit inflammation, induce immune cells into a regulatory phenotype and stimulate tissue repair, mesenchymal stromal cells (MSCs) represent a promising therapy for severe and critical COVID-19 disease, which is associated with an uncontrolled immune-mediated inflammatory response. Methods In this phase I-II trial, we aimed to evaluate the safety and efficacy of 3 intravenous infusions of bone marrow (BM)-derived MSCs at 3-day intervals in patients with severe COVID-19. All patients also received dexamethasone and standard supportive therapy. Between June 2020 and September 2021, 8 intensive care unit patients requiring supplemental oxygen (high-flow nasal oxygen in 7 patients, invasive mechanical ventilation in 1 patient) were treated with BM-MSCs. We retrospectively compared the outcomes of these MSC-treated patients with those of 24 matched control patients. Groups were compared by paired statistical tests. Results MSC infusions were well tolerated, and no adverse effect related to MSC infusions were reported (one patient had an ischemic stroke related to aortic endocarditis). Overall, 3 patients required invasive mechanical ventilation, including one who required extracorporeal membrane oxygenation, but all patients ultimately had a favorable outcome. Survival was significantly higher in the MSC group, both at 28 and 60 days (100% vs 79.2%, p = 0.025 and 100% vs 70.8%, p = 0.0082, respectively), while no significant difference was observed in the need for mechanical ventilation nor in the number of invasive ventilation-free days, high flow nasal oxygenation-free days, oxygen support-free days and ICU-free days. MSC-treated patients also had a significantly lower day-7 D-dimer value compared to control patients (median 821.0 µg/L [IQR 362.0-1305.0] vs 3553 µg/L [IQR 1155.0-6433.5], p = 0.0085). Conclusions BM-MSC therapy is safe and shows very promising efficacy in severe COVID-19, with a higher survival in our MSC cohort compared to matched control patients. These observations need to be confirmed in a randomized controlled trial designed to demonstrate the efficacy of BM-MSCs in COVID-19 ARDS. Clinical Trial Registration (www.ClinicalTrials.gov), identifier NCT04445454